ANALISIS YURIDIS TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 34/PUU-XI/2013 TENTANG PENGUJIAN UNDANG-UNDANG NOMOR 08 TAHUN 1981 TENTANG HUKUM ACARA PIDANA TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Faishal Taufiqurrahman; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Legal effort constitutes protected right by the law aimed to seek the truth and justice. Legal effort consist of the First Instance Court, Appeal, Supreme Court Appeal, and Cotemplation Review to the Supreme Court. By the existence of decision number 34/PUU-XI/2013 born phenomenon related to how the legal guarantee of the parties. Antasari Azhar’s caserelated to Contemplation Review to Supreme Court and Supreme Court decided to refuse that Comtemplation Review. The Supreme Court should be the final decision, but by the Contitutional Court’s decision ring about problem about the legal assurance on the Contemplation Review. The aims of this research are to seek the basic consideration of Constitutional Court in deciding the case number 34/PUU-XI/2013 and to seek the implication of the decision taken by the Constitutional Court to the principle of legal assurance and to seek the follow up of the decision number 34/PUU/XI/2013 to the Indonesian Judicature. Research used is also called normative or literature legal research. Because using the literature as a major cornerstone in conducting this research. The result of this research consist of, first: the basic consideration of Constitutional Court deciding lawsuit number 34/PUU-XI/2013 was based on sense of justice and human right. Second: implication of Constitutional Court number 34/PUU-XI/2013 to the legal assurance did not affect the void of the legal assurance as the court decision if had permanen legal power, it has legal assurance. Third: the follow up of the decision of Constitutional Court number 34/PUU-XI/2013 was that regulation formulation technically on the proposing the new proof (novum) and the space time of proposing legal effort of Contemplation Review must be made by a concrete regulation. Suggestions of the writer consist of, first: to the legislator should amend the articles existed in KUHAP which has been judicial review by Supreme Court. Second: to the legislator should make clear regulation in which kind of the new proof (novum) could be proposed to Contemplation Review more than one. Third: the proposal of Contemplation Review should be stated the limitation and space time given in order to create legal assurance, justice and usefull.Keywords : Juridical Analysis – Decision Constitutional Court - KUHAP